Method for detecting different types of oxygen elements in silicon carbide material
Patent Information
- Application Number
- CN202311200147.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-09-15
AI Technical Summary
[0004]目前研究SiC纤维中氧元素含量变化仅局限在总氧含量变化层面,对不同类型氧含量变化并未开展相关工作
[0031]与现有技术相比,本发明的优点包括:
Smart Images

Figure CN117288805B_ABST
Abstract
Description
Technical Field
[0001] This invention specifically relates to a method for detecting different types of oxygen elements in silicon carbide materials, belonging to the field of analytical testing technology. Background Technology
[0002] Continuous silicon carbide (SiC) fibers possess excellent high-temperature resistance, oxidation resistance, creep resistance, corrosion resistance, and radiation resistance, making them an important reinforcement for the preparation of high-temperature ceramic matrix composites (CMCs). CMCs are widely used in harsh environments such as high temperature, corrosion, and radiation, playing a crucial role in high-tech weaponry, aerospace, and the nuclear industry. With the increasing application of CMCs in extreme environments such as the nuclear industry, there is a pressing need for higher strength, temperature resistance, and oxidation resistance in SiC fibers. Therefore, the research and development of high-strength, high-thermal-conductivity, high-temperature-resistant, and oxidation-resistant SiC fibers, especially third-generation SiC fibers, is of great significance.
[0003] The precursor conversion method for preparing continuous SiC fibers generally involves the following four steps: precursor synthesis, spinning, organic fiber infusibility, and high-temperature firing and sintering. The process from the precursor polyaluminosilicate (PACS) to highly crystalline, near-stoichiometric SiC fibers requires the introduction of a suitable amount of oxygen (7-15 wt%) through air infusibility, followed by pyrolysis and inorganication at approximately 1300℃ to obtain the intermediate product Si-CO(Al) fibers, which are mainly composed of amorphous SiC. x O y The oxygen-rich carbon fibers, composed of a phase, begin to show β-SiC microcrystals, which grow slowly, and then are processed using SiC at around 1500℃. x O y Phase decomposition produces SiO and CO, removing impurity oxygen and excess carbon. At this point, the fiber crystallinity increases significantly. Finally, the fiber is densified at a higher temperature, resulting in sintered SiC fiber. At this stage, the SiC grain structure is complete and regularly arranged, forming β-SiC polycrystalline material with a near-stoichiometric composition (oxygen content < 1 wt%). In the preparation process of third-generation SA-type SiC fiber, from the organic precursor structure to the inorganic SiC structure, a large amount of oxygen is introduced in the infusible stage and then removed during the high-temperature sintering stage, ultimately transforming into near-stoichiometric SiC polycrystalline material. Oxygen plays a crucial role throughout the entire preparation process, with its chemical bonding form evolving and its content undergoing significant changes. In particular, during the crystallization and densification stage, lattice oxygen and grain boundary oxygen directly affect the fiber's grain growth, composition, and structure. Therefore, studying the changes in the content of different types of oxygen throughout the SiC fiber preparation process is of great significance for establishing the structure-property relationship between lattice oxygen, grain boundary oxygen, and the fiber's mechanical and thermal conductivity properties.
[0004] Current research on changes in oxygen content in SiC fibers is limited to changes in total oxygen content, and no work has been done on changes in different types of oxygen content. Summary of the Invention
[0005] In view of the shortcomings of the prior art, the purpose of this invention is to provide a method for detecting different types of oxygen elements in silicon carbide materials.
[0006] To achieve the aforementioned objectives, the technical solution adopted by this invention includes:
[0007] This invention provides a method for detecting different types of oxygen elements in silicon carbide materials, comprising:
[0008] The first step includes:
[0009] S1. Heating multiple oxygen standards in a gradient heating manner, and recording the temperature and time corresponding to the release of different types of oxygen elements contained in the multiple oxygen standards.
[0010] S2. Etching multiple oxygen standards with acid to remove different types of oxygen elements contained in the multiple oxygen standards, heating the etched multiple oxygen standards respectively with the gradient heating method, and also recording the temperature and time corresponding to the release of different types of oxygen elements contained in the etched multiple oxygen standards.
[0011] S3. Compare the test results obtained in step S1 with the test results obtained in step S2, and establish characteristic temperature curves for different types of oxygen elements accordingly.
[0012] The second step includes: heating the silicon carbide material to be tested using the gradient heating method, and recording the temperature, time and intensity of the release of different types of oxygen elements contained in the silicon carbide material, and establishing the relationship curve between the release temperature and / or time of different types of oxygen elements and the release intensity of different types of oxygen elements.
[0013] The third step includes: comparing the relationship curve obtained in the second step with the characteristic temperature curve obtained in the first step to achieve qualitative detection of different types of oxygen elements in the silicon carbide material.
[0014] In some embodiments, the detection method further includes:
[0015] The fourth step includes: heating the metal oxide standard in the gradient heating method and recording the temperature, time and intensity at which the oxygen element contained in the metal oxide standard is released, thereby establishing a standard working curve;
[0016] The fifth step includes: comparing the relationship curve obtained in the second step with the standard working curve obtained in the fourth step to achieve quantitative detection of different types of oxygen elements in the silicon carbide material.
[0017] Furthermore, the various oxygen standards include surface oxygen standards, amorphous oxygen standards, grain boundary oxygen standards, and lattice oxygen standards, and the different types of oxygen elements include surface oxygen, amorphous oxygen, grain boundary oxygen, and lattice oxygen.
[0018] In some embodiments, the surface oxygen standard includes one or more of the following: steel standard, copper standard, zinc scrap standard, iron powder standard, titanium powder standard, nickel sheet standard, and metal alloy standard.
[0019] In some embodiments, the amorphous oxygen standard includes one or more of electron beam crosslinked SiC fibers, electron beam crosslinked SiC blocks, electron beam crosslinked SiC powder, thermally crosslinked SiC fibers sintered at 1000℃~1800℃, thermally crosslinked SiC blocks sintered at 1000℃~1800℃, and thermally crosslinked SiC powder sintered at 1000℃~1800℃.
[0020] In some embodiments, the grain boundary oxygen standard includes one or more of the following: SA type SiC fiber, high-temperature sintered SiC fiber containing heterogeneous elements (including aluminum, boron, titanium, zirconium, iron, cobalt, nickel, yttrium, and titanium), SiC bulk material, and SiC powder.
[0021] In some embodiments, the lattice oxygen standard includes one or more of the following: high-purity SiC (powder, bulk, fiber), high-purity silicon nitride sample (powder, bulk, fiber), high-purity aluminum oxide, high-purity tungsten carbide, high-purity titanium carbide, and high-purity tantalum carbide sample.
[0022] In some embodiments, the acid includes one or more of HF, H2SO4, HCl, HNO3, HClO4, and H3PO4.
[0023] In some preferred embodiments, the acid includes one or a combination of two of HF and H2SO4.
[0024] In some embodiments, step S1 specifically includes: using an oxygen and nitrogen analyzer to heat multiple oxygen standards with an initial power of 0-100W, a degassing cycle of 3-5, a termination power of 5000-5800W, a heating time of 15-25s, a holding time of 500-700s, and a cooling time of 6-20s, and recording the temperature and time corresponding to the release of different types of oxygen elements contained in the multiple oxygen element standards.
[0025] In some embodiments, step S2 specifically includes: etching multiple oxygen standards with 10-49 wt% HF at 30-90°C for 1-10 hours, and then etching multiple oxygen standards with 40-98 wt% H2SO4 at 80-200°C for 1-24 hours to remove different types of oxygen elements contained in the multiple oxygen standards; heating the etched multiple oxygen standards respectively using the heating method in step S1; and also recording the temperature and time corresponding to the release of different types of oxygen elements contained in the etched multiple oxygen standards.
[0026] In some embodiments, step S3 specifically includes: comparing the test results obtained in step S1 with the test results obtained in step S2, and establishing characteristic temperature curves for different types of oxygen elements with temperature or time as the horizontal axis and oxygen release intensity as the vertical axis.
[0027] In some embodiments, the metal oxide standard includes any one of yttrium oxide, zirconium oxide, niobium oxide, strontium oxide, cerium oxide, titanium dioxide, uranium dioxide, calcium oxide, magnesium oxide, aluminum oxide, lanthanum oxide, lutetium oxide, and thorium dioxide, but is not limited thereto.
[0028] Furthermore, the fourth step specifically includes: first calcining the metal oxide standard at a temperature above 1000°C for more than 2 hours in an oxygen-containing atmosphere, and then heating the metal oxide standard in the gradient heating method to establish the standard working curve.
[0029] In some embodiments, the silicon carbide material is selected from any one of silicon carbide fiber, silicon carbide precursor, silicon carbide oxide fiber, silicon carbide infusible fiber, ceramic fiber, silicon carbide powder, and silicon carbide bulk, but is not limited thereto.
[0030] Furthermore, the silicon carbide material is selected from any one of polycarbosilane, polyaluminocarbosilane, polyboronocarbosilane, polyboronosilazane, polyyttrium carbosilane, polyzirconium carbosilane, polytitanium carbosilane, polycarbosilazane, polysilicon propylene, boron nitride, silicon nitride, polyboronosilane, polycarbosilane air-insoluble fiber, polycarbosilane thermally crosslinked fiber, and polyaluminocarbosilane fiber, and is not limited thereto.
[0031] Compared with the prior art, the advantages of the present invention include:
[0032] (1) By using thermal analysis methods, the types and contents of oxygen elements in the sample can be distinguished by the different bond energies of different types of oxygen elements, providing a new characterization method for the study of silicon carbide materials.
[0033] (2) In the process of preparing silicon carbide materials with precursors, it is possible to distinguish different types of oxygen elements and calculate the content of different types of oxygen elements, so as to quantitatively study the evolution process of different bonding forms of different types of oxygen elements from organic to inorganic structures and the content variation law, which helps to study the influence of different types of oxygen elements on the performance of silicon carbide materials and provides a research basis for the preparation of high-performance silicon carbide materials. Attached Figure Description
[0034] Figure 1 This is a flowchart illustrating a method for measuring the content of different types of oxygen elements in silicon carbide materials according to the present invention.
[0035] Figure 2 This is the characteristic temperature curve in Embodiment 2 of the present invention;
[0036] Figure 3 This is a characteristic temperature curve from Comparative Example 1 of the present invention. Detailed Implementation
[0037] In view of the shortcomings of the prior art, the inventors of this case, through long-term research and extensive practice, have proposed the technical solution of this invention. The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0038] This invention patent aims to establish a bond energy-related thermal analysis method to distinguish different types of oxygen and accurately determine their content, representing an innovation in the characterization of SiC materials. Furthermore, focusing on oxygen, it achieves effective differentiation and accurate determination of surface oxygen, amorphous oxygen, lattice oxygen, and grain boundary oxygen during the preparation of precursor SiC ceramic materials. This allows for quantitative research on the evolution of different bonding morphologies of oxygen elements from organic to inorganic structures and their content variations, contributing to the study of the influence of lattice oxygen and grain boundary oxygen on the properties of SiC ceramic materials and providing a research foundation for the preparation of high-performance SiC materials.
[0039] Utilizing the different bond energies of oxygen elements in different crystal types (bond energy order: surface oxygen < amorphous oxygen < grain boundary oxygen < lattice oxygen), and based on a high-temperature oxygen, nitrogen, and hydrogen analyzer, the temperature gradient is changed by a control system. As the temperature gradually increases, the chemical bonds of surface oxygen, amorphous oxygen, grain boundary oxygen, and lattice oxygen break sequentially, forming a curve with temperature and time as the x-axis and the release intensity of different types of oxygen elements as the y-axis. HF and H2SO4 can etch away surface oxygen, amorphous oxygen, and grain boundary oxygen at certain temperatures and concentrations. By comparing the oxygen element curves of samples before and after etching and verifying with standards, characteristic temperature curves of different types of oxygen are obtained. The accurate content of oxygen is determined by oxygen standards, and the oxygen and nitrogen analyzer accurately calculates the content of different types of oxygen through integration. Through the above experimental method, the differentiation and accurate determination of different types of oxygen in precursor conversion ceramics are achieved. The method provided by this invention is simple to operate, convenient and quick. The characteristic temperature curves of different types of oxygen on different oxygen and nitrogen analyzers can be determined by changing the instrument parameters. The characteristic peak positions of different types of oxygen can be determined by changing the instrument parameters. Subsequent experiments can be carried out by directly calling existing methods, which provides a new characterization method for SiC materials.
[0040] In this embodiment of the invention, four samples were used: commercial steel standard, electron beam cross-linked SiC fiber from Fujian Liya New Materials Co., Ltd., high-purity SiC powder from Sinopharm Group, and SA-type SiC fiber from Ube Industries, Japan. A certain amount of each of the four samples was tested using a high-temperature oxygen, nitrogen, and hydrogen analyzer with a pre-programmed heating program. The analyzer's heating program included both one-step heating and programmed heating modes, and the optimal experimental conditions were determined through parameter exploration and optimization. The optimized parameters mainly included: initial power, isothermal time, heating rate, carrier gas flow rate, degassing time, and cooling time. Ultimately, the separation of oxygen on the sample surface, amorphous oxygen, lattice oxygen, and grain boundary oxygen was achieved, and the content of each type of oxygen was calculated by integrating the area. Then, three standard samples—Liya SiC fiber, high-purity SiC, and SA-type SiC fiber—were etched using HF and H2SO4 at appropriate temperatures and concentrations to remove surface oxygen, amorphous oxygen, and grain boundary oxygen. Lattice oxygen will be displayed on the curve. Steel standard samples verify the location of surface oxygen, Liya samples verify amorphous oxygen, high-purity SiC samples verify lattice oxygen, and SA samples verify grain boundary oxygen. The entire research process described above allows for the differentiation of surface oxygen, lattice oxygen, amorphous oxygen, and grain boundary oxygen in SiC ceramic materials. Oxygen content was calibrated using Y2O3 and steel standard samples with different oxygen contents. The above experimental process enables the differentiation of different types of oxygen and the accurate determination of their content. A schematic diagram of the scheme is shown below. Figure 1 As shown.
[0041] The following examples illustrate the method for measuring different oxygen element types and their contents in silicon carbide materials provided by the present invention. These examples should not be construed as limiting the scope of protection of the present invention.
[0042] Example 1
[0043] This embodiment uses four samples: commercial steel standard, electron beam cross-linked SiC fiber from Fujian Liya New Materials Co., Ltd., high-purity SiC powder from Sinopharm Group, and SA-type SiC fiber from Ube Industries, Japan. 20 mg of each of the four samples were analyzed using a programmed temperature rise method on an Oxygen and Nitrogen Analyzer (ON836) from Leco Corporation, USA. By changing the instrument parameters, effective separation of surface oxygen, amorphous oxygen, lattice oxygen, and grain boundary oxygen was achieved. The determined parameters were: initial power 20W; furnace degassing cycle 3; termination power 5700W; heating time 25s; cooling time 20s; and holding time 600s.
[0044] Three standard samples—Liya SiC fiber, high-purity SiC, and SA-type SiC fiber—were etched using 36 wt% HF in an 80°C water bath for 8 hours. After etching, the samples were cleaned alternately with deionized water and ethanol using a centrifuge until neutral. The samples were then further etched using 98 wt% H2SO4 in a 150°C oil bath for 10 hours. After etching, the samples were cleaned alternately with deionized water and ethanol until neutral. The samples were then dried in an 80°C oven and ready for use.
[0045] 20mg samples were accurately weighed before and after etching, and comparative experiments were conducted according to the oxygen and nitrogen analyzer parameters set above. The steel standard sample can obtain the characteristic temperature curve of surface oxygen, the Liya sample can obtain the characteristic temperature curve of amorphous oxygen, the high-purity SiC sample can obtain the characteristic temperature curve of lattice oxygen, and the SA sample can obtain the characteristic temperature curve of grain boundary oxygen. Thus, characteristic temperature curves of different types of oxygen can be established, which are the standard working curves of oxygen elements.
[0046] Yttrium oxide was used as the oxygen content, which was 21.26%. Before use, the yttrium oxide was calcined in an air atmosphere at 1000℃ for at least 2 hours to remove impurities and moisture. Then, the temperature was increased according to the oxygen, nitrogen and hydrogen analyzer parameters set above, the characteristic temperature curve of oxygen element was calibrated, and the content of different types of oxygen element was calculated.
[0047] The precursor treated at 1200℃ was converted into silicon carbide fiber and ground into powder. Approximately 20 mg of the ground sample was accurately weighed and measured using an oxygen, nitrogen, and hydrogen analyzer with the above-mentioned parameters. The oxygen content of different types of SiC fibers was obtained, and the data are as follows (SiC at 1200℃ has not yet crystallized, so there is no grain boundary or lattice oxygen).
[0048] Table 1. Test results of oxygen content (wt%) of different types of silicon carbide fibers after precursor conversion at 1200℃.
[0049] 1 0.0060 10.17 / / 2 0.0059 10.15 / / 3 0.0059 10.20 / / average value 0.0059 10.17 / /
[0050] Example 2
[0051] In this embodiment, three standard samples—Lia SiC fiber, high-purity SiC, and SA-type SiC fiber—were etched using 30wt% HF in an 80℃ water bath. After etching for 10 hours, the samples were washed with deionized water using a centrifuge until neutral. The samples were then further etched using 80wt% H2SO4 in a 170℃ oil bath for 8 hours. After etching, the samples were washed alternately with deionized water and ethanol until neutral. The samples were then dried in an 80℃ oven and taken for later use.
[0052] 20 mg of samples were accurately weighed before and after etching, and a comparative experiment was conducted according to the oxygen and nitrogen analyzer parameters set in Example 1. The characteristic temperature curve of surface oxygen can be obtained for steel standard sample, the characteristic temperature curve of amorphous oxygen can be obtained for Liya sample, the characteristic temperature curve of lattice oxygen can be obtained for high-purity SiC sample, and the characteristic temperature curve of grain boundary oxygen can be obtained for SA sample. Thus, characteristic temperature curves of different types of oxygen can be established, which are the standard working curves of different oxygen elements.
[0053] Zirconia metal was used as the standard, with an oxygen content of 25.97%. Before use, the zirconia was calcined in an air atmosphere at 1000°C for at least 2 hours to remove impurities and moisture. The oxygen content was calibrated according to the oxygen, nitrogen and hydrogen analyzer parameters set in Example 1.
[0054] The precursor treated at 1500℃ was converted into silicon carbide fibers and ground into powder. Approximately 20 mg of the ground sample was accurately weighed, and the oxygen content of different types of SiC fibers was determined using the experimental method for different types of oxygen content in Example 1. The data are as follows:
[0055] Table 2. Test results of oxygen content (wt%) of different types of silicon carbide fibers after precursor conversion at 1500℃.
[0056] 1 0.0307 1.26 0.08 0.104 2 0.0308 1.25 0.08 0.104 3 0.0307 1.28 0.09 0.104 average value 0.0307 1.26 0.08 0.104
[0057] Example 3
[0058] In this embodiment, three standard samples—Lia SiC fiber, high-purity SiC, and SA-type SiC fiber—were etched using 40% HF in an 80°C water bath for 8 hours. After etching, the samples were washed with deionized water using a centrifuge until neutral. The samples were then further etched using 98% H2SO4 in a 150°C oil bath for 10 hours. After etching, the samples were washed with deionized water until neutral and dried in an 80°C oven for later use.
[0059] 20 mg of samples were accurately weighed before and after etching, and comparative experiments were conducted according to the oxygen and nitrogen analyzer parameters set above. Characteristic temperature curves of surface oxygen were obtained for steel standard samples, characteristic temperature curves of amorphous oxygen were obtained for Liya samples, characteristic temperature curves of lattice oxygen were obtained for high-purity SiC samples, and characteristic temperature curves of grain boundary oxygen were obtained for SA samples. Characteristic temperature curves of different types of oxygen can be established, which are the standard working curves of different oxygen elements.
[0060] Yttrium oxide was used as the standard, with an oxygen content of 21.26%. Before use, yttrium oxide was calcined in an air atmosphere at 1000°C for at least 2 hours to remove impurities and moisture. Then, the oxygen content was calibrated according to the oxygen and nitrogen analyzer test method in Example 1.
[0061] The precursor treated at 1800℃ was converted into silicon carbide fibers and ground into powder. Approximately 20 mg of the ground sample was accurately weighed, and the oxygen content of different types of SiC fibers was determined using the experimental method for different types of oxygen content in Example 1. The data are as follows:
[0062] Table 3. Test results of oxygen content (wt%) of different types of silicon carbide fibers after precursor conversion at 1800℃.
[0063] 1 / 0.06 0.44 0.03 2 / 0.08 0.43 0.03 3 / 0.06 0.45 0.03 average value / 0.07 0.44 0.03
[0064] Example 4
[0065] In this embodiment, three standard samples—Lia SiC fiber, high-purity SiC, and SA-type SiC fiber—were etched using 49 wt% HF in an 80°C water bath for 10 hours. The samples were then washed with deionized water using a centrifuge until neutral. The samples were then further etched using 90 wt% H2SO4 in an 180°C oil bath for another 10 hours. After etching, the samples were washed with deionized water until neutral and then dried in an 80°C oven for later use.
[0066] 20 mg of samples were accurately weighed before and after etching, and comparative experiments were conducted according to the oxygen and nitrogen analyzer parameters set above. Characteristic temperature curves of surface oxygen were obtained for steel standard samples, characteristic temperature curves of amorphous oxygen were obtained for Liya samples, characteristic temperature curves of lattice oxygen were obtained for high-purity SiC samples, and characteristic temperature curves of grain boundary oxygen were obtained for SA samples. Characteristic temperature curves of different types of oxygen can be established, which are the standard working curves of different oxygen elements.
[0067] Zirconia was used as the standard, with an oxygen content of 25.97%. Before use, the zirconia was calcined in an air atmosphere at 1000°C for at least 2 hours to remove impurities and moisture. Then, the oxygen content was calibrated according to the oxygen and nitrogen analyzer test method in Example 1.
[0068] Approximately 50 mg of high-purity SiC powder sample was accurately weighed, and the oxygen content of different types of SiC powder was determined using the experimental method for different types of oxygen content in Example 1. The data are as follows:
[0069] Table 4. Test results of oxygen content (wt%) of different types of silicon carbide powder
[0070]
[0071]
[0072] Example 5
[0073] Three standard samples—Lia SiC fiber, high-purity SiC, and SA-type SiC fiber—were etched using 32wt% HF in an 80℃ water bath for 10 hours. The samples were then washed with deionized water using a centrifuge until neutral. The samples were then further etched using 85wt% H2SO4 in an 180℃ oil bath for 10 hours. After etching, the samples were washed with deionized water until neutral and then dried in an 80℃ oven for later use.
[0074] 20 mg of samples were accurately weighed before and after etching, and comparative experiments were conducted according to the oxygen and nitrogen analyzer parameters set above. Characteristic temperature curves of surface oxygen were obtained for steel standard samples, characteristic temperature curves of amorphous oxygen were obtained for Liya samples, characteristic temperature curves of lattice oxygen were obtained for high-purity SiC samples, and characteristic temperature curves of grain boundary oxygen were obtained for SA samples. Characteristic temperature curves of different types of oxygen can be established, which are the standard working curves of different oxygen elements.
[0075] Zirconia metal was used as the standard, with an oxygen content of 25.97%. Before use, the zirconia was calcined in an air atmosphere at 1000°C for at least 2 hours to remove impurities and moisture. The oxygen content was calibrated according to the oxygen and nitrogen analyzer test method in Example 1.
[0076] The polyaluminum carbide silane air-insoluble fiber, which had been thermally cross-linked at 450℃, was ground into powder. Approximately 20 mg of the ground sample was accurately weighed, and the oxygen content of different types of polyaluminum carbide silane air-insoluble fiber was determined using the experimental method for different types of oxygen content in Example 1. The data are as follows:
[0077] Table 5. Test results of oxygen content (wt%) of different types of polyaluminum carbide silane air-insoluble fiber
[0078] 1 0.44 7.90 / / 2 0.43 7.80 / / 3 0.44 7.94 / / average value 0.44 7.88 / /
[0079] Comparative Example 1
[0080] The oxygen and nitrogen analyzer (Likely ON836) was tested under the following conditions according to traditional experimental methods: furnace degassing cycle 3; power 5900W; heating time 15s; cooling time 6s; power mode: constant temperature; analysis power 5500W.
[0081] Three standard samples—Lia SiC fiber, high-purity SiC, and SA-type SiC fiber—were etched using 40 wt% HF in an 80°C water bath. After etching for 8 hours, the samples were washed with deionized water using a centrifuge until neutral. The samples were then etched for another 10 hours using 98 wt% H2SO4 in a 150°C oil bath. After etching, the samples were washed with deionized water until neutral. The samples were then dried in an 80°C oven and taken for later use.
[0082] 20 mg of samples were accurately weighed before and after etching, and comparative experiments were conducted according to the oxygen and nitrogen analyzer parameters set above. Characteristic temperature curves of surface oxygen were obtained for steel standard samples, characteristic temperature curves of amorphous oxygen were obtained for Liya samples, characteristic temperature curves of lattice oxygen were obtained for high-purity SiC samples, and characteristic temperature curves of grain boundary oxygen were obtained for SA samples. Characteristic temperature curves of different types of oxygen can be established, which are the standard oxygen element working curves.
[0083] Yttrium oxide was used as the standard, with an oxygen content of 21.26%. Before use, yttrium oxide needs to be calcined in an air atmosphere at 1000℃ for at least 2 hours to remove impurities and moisture. The oxygen content was then calibrated according to the oxygen and nitrogen analyzer test method described above.
[0084] Precursor-converted silicon carbide fibers treated at 1200℃ were ground into powder. Approximately 20 mg of the ground sample was accurately weighed, and the oxygen content of different types of SiC fibers was determined using the aforementioned experimental methods for different types of oxygen content. The data are as follows:
[0085] Table 6. Test results of oxygen content (wt%) of different types of silicon carbide fibers after precursor conversion at 1200℃.
[0086] 1 / / / / 10.18 2 / / / / 10.20 3 / / / / 10.24 average value / / / / 10.21
[0087] The oxygen content of different types of silicon carbide materials was analyzed using an oxygen-nitrogen analyzer. Please refer to the representative experimental figures in Examples 1-5. Figure 2 The experimental spectrum comparing the oxygen content of silicon carbide materials in Example 1 is shown below. Figure 3 , Figure 2 , Figure 3 The horizontal axis represents time, the vertical axis represents peak intensity, and the peak integral area represents oxygen content. Figure 2 Comparison Figure 3A comparison reveals that, using the same etching method and the same standard samples, the comparative examples employ traditional oxygen and nitrogen analyzer experimental methods, while Examples 1-5 use experimental conditions with different types of oxygen content, resulting in completely different results. Comparative Example 1 can only test the total oxygen content of the sample, not the different types of oxygen content, while Examples 1-5 provide the content of surface oxygen and amorphous oxygen in the sample, with high repeatability and accuracy. Through the above Examples 1-5, it can also be seen that the present invention exhibits good parallelism and data stability for testing different types of oxygen content.
Claims
1. A method for detecting different types of oxygen elements in silicon carbide materials, characterized in that, include: The first step includes: S1. Heating multiple oxygen standards in a gradient heating manner, and recording the temperature and time corresponding to the release of different types of oxygen elements contained in the multiple oxygen standards. S2. Etching multiple oxygen standards with acid to remove different types of oxygen elements contained in the multiple oxygen standards, heating the etched multiple oxygen standards respectively with the gradient heating method, and also recording the temperature and time corresponding to the release of different types of oxygen elements contained in the etched multiple oxygen standards. S3. Compare the test results obtained in step S1 with the test results obtained in step S2, and establish characteristic temperature curves for different types of oxygen elements accordingly. The second step includes: heating the silicon carbide material to be tested using the gradient heating method, and recording the temperature, time and intensity of the release of different types of oxygen elements contained in the silicon carbide material, and establishing the relationship curve between the release temperature and / or time of different types of oxygen elements and the release intensity of different types of oxygen elements. The third step includes: comparing the relationship curve obtained in the second step with the characteristic temperature curve obtained in the first step to achieve qualitative detection of different types of oxygen elements in the silicon carbide material.
2. The detection method according to claim 1, characterized in that: The various oxygen standards include surface oxygen standards, amorphous oxygen standards, grain boundary oxygen standards, and lattice oxygen standards, and the different types of oxygen elements include surface oxygen, amorphous oxygen, grain boundary oxygen, and lattice oxygen.
3. The detection method according to claim 2, characterized in that: The surface oxygen standard includes one or more of the following: steel standard, copper standard, zinc scrap standard, iron powder standard, titanium powder standard, nickel sheet standard, and metal alloy standard. And / or, the amorphous oxygen standard includes one or more of the following: electron beam crosslinked SiC fiber, electron beam crosslinked SiC block, electron beam crosslinked SiC powder, thermally crosslinked SiC fiber sintered at 1000℃~1800℃, thermally crosslinked SiC block sintered at 1000℃~1800℃, and thermally crosslinked SiC powder sintered at 1000℃~1800℃. And / or, the grain boundary oxygen standard includes one or more of SA-type SiC fibers, high-temperature sintered SiC fibers containing heterogeneous elements, and SiC bulk and SiC powder, wherein the heterogeneous elements include one or more of aluminum, boron, titanium, zirconium, iron, cobalt, nickel, yttrium, and titanium. And / or, the lattice oxygen standard includes one or more of the following: high-purity SiC sample, high-purity silicon nitride sample, high-purity aluminum oxide, high-purity tungsten carbide, high-purity titanium carbide, and high-purity tantalum carbide sample.
4. The detection method according to claim 1, characterized in that: The acid includes one or more of HF, H2SO4, HCl, HNO3, HClO4, and H3PO4.
5. The detection method according to claim 4, characterized in that: The acid is one or a combination of two of HF and H2SO4.
6. The detection method according to claim 1, characterized in that: Step S1 specifically includes: using an oxygen and nitrogen analyzer to heat multiple oxygen standards with an initial power of 0-100W, a degassing cycle of 3-5, a termination power of 5000-5800W, a heating time of 15-25s, a holding time of 500-700s, and a cooling time of 6-20s, and recording the temperature and time corresponding to the release of different types of oxygen elements contained in the multiple oxygen standards; Step S2 specifically includes: etching the various oxygen standards with 10-49wt% HF at 30-90℃ for 1-10h, and then etching the various oxygen standards with 40-98wt% H2SO4 at 80-200℃ for 1-24h to remove the different types of oxygen elements contained in the various oxygen standards; heating the etched oxygen standards in the same way as in step S1; and recording the temperature and time corresponding to the release of the different types of oxygen elements contained in the etched oxygen standards. Step S3 specifically includes: comparing the test results obtained in step S1 with the test results obtained in step S2, and establishing characteristic time or temperature curves for different types of oxygen elements with time or temperature as the horizontal axis and oxygen release intensity as the vertical axis.
7. The detection method according to claim 1, characterized in that, Also includes: The fourth step includes: The metal oxide standard is heated using the gradient heating method, and the temperature, time and intensity of oxygen release from the metal oxide standard are recorded to establish a standard working curve. The fifth step includes: The relationship curve obtained in the second step is compared with the standard working curve obtained in the fourth step to achieve quantitative detection of different types of oxygen elements in the silicon carbide material.
8. The detection method according to claim 7, characterized in that: The metal oxide standards include any one of yttrium oxide, zirconium oxide, niobium oxide, strontium oxide, cerium oxide, titanium dioxide, uranium dioxide, calcium oxide, magnesium oxide, aluminum oxide, lanthanum oxide, lutetium oxide, and thorium dioxide.
9. The detection method according to claim 7, characterized in that, The fourth step specifically includes: first, calcining the metal oxide standard at a temperature above 1000°C for more than 2 hours in an oxygen-containing atmosphere, and then heating the metal oxide standard using the gradient heating method to establish the standard working curve.
10. The detection method according to claim 1, characterized in that: The silicon carbide material is selected from any one of silicon carbide fiber, silicon carbide precursor, silicon carbide oxide fiber, silicon carbide non-fusible fiber, ceramic fiber, silicon carbide powder, and silicon carbide bulk.
11. The detection method according to claim 10, characterized in that: The silicon carbide material is selected from any one of polycarbosilane, polyaluminocarbosilane, polyboronocarbosilane, polyboronosilazane, polyyttrium carbosilane, polyzirconium carbosilane, polytitanium carbosilane, polycarbosilazane, polysilicon propylene, boron nitride, silicon nitride, polyboronosilane, polycarbosilane air-insoluble fiber, polycarbosilane thermally crosslinked fiber, and polyaluminocarbosilane fiber.
Citation Information
Patent Citations
Method for detecting oxygen content in silicon carbide
CN106290809A
Method for determining oxygen content in silicon carbide ceramic material
CN111257267A